UPAYA PEMBENTUKAN KARAKTER MELALUI PERMAINAN TRADISIONAL DI SDN 6 SENGKAE KECAMATAN BUNGORO KABUPATEN PANGKAJENE DAN KEPULAUAN - Nurlaela .; Rego Devilla; Elpisah . (STKIP Pembangunan Indonesia Makassar, 2022)
The purpose of this research is to 1.) To analyze the character building efforts of SDN 6 Sengkae Kec. Bungoro Kab. Pangkep through traditional games, 2) Analyzing the influence of the character building of students at SDN 6 Sengkae Kec. Bungoro Kab. Pangkep through traditional games. This type of research is descriptive research using a qualitative approach. The research subjects were teachers and students. Data collection techniques, namely interviews, observation, and documentation and were analyzed using the Miles and Huberman model, namely data reduction, data display, and drawing conclusions. The results of the study show that character building through traditional games at SDN 6 Sengkae, Bungoro District, Pangkajene and Islands District is through three components, namely moral knowing, moral feeling, and moral action. Furthermore, the stages carried out are 1) introducing good values, giving the benefits of good values, and teaching people to do good things based on values. In addition, giving if it is not in accordance with the value of goodness, giving a warning because it is not based on the value of goodness, being a role model for students to practice good values by telling the truth, 2) The impact of traditional games on character building is customary courtesy. Instilling good values in elementary school children can take practice. Habituation is carried out routinely by the teacher every day to help children become accustomed to good behavior. This custom is also used when playing traditional games. Based on the results of research conducted by the author, there are several suggestions that the author can convey.Keywords: Character, Traditional Games